Apixaban versus enoxaparin to prevent venous thromboembolism in post-operative patients with gynecologic cancers at an urban academic medical center - Victoria Diamond; Katherine Gerber; Geno Merli; Rebecca Mercier; Aaron Shafer; Norman Rosenblum (Elsevier, 2024)
Objective: A recent clinical trial demonstrated that the use of apixaban was safe and equal to enoxaparin (LMWH) in post-operative gynecologic oncology patients. This study aimed to determine if these findings are applicable in a diverse patient population at a single site urban academic medical center. Methods: This was a retrospective cohort study of patients who underwent an exploratory laparotomy for confirmed or presumed gynecologic cancer from the years 2017-2023 at a single-site urban academic medical center. Venous thromboembolism (VTE) prophylaxis with LMWH was standard practice at our institution up until January 2021 after which apixaban became standard for post-operative prophylaxis in our division. Baseline demographic and clinical characteristics of patients receiving apixaban post-operatively were compared to the population previously receiving enoxaparin. The primary outcome was a VTE event within 90 days of surgery. Secondary outcomes included major and minor bleeding events. Results: Two hundred fifteen patients met inclusion criteria, of which 65 were discharged on enoxaparin and 150 were discharged on apixaban. Baseline characteristics in terms of age, race/ethnicity and BMI found no significant difference between the two groups. Rates of any VTE event within 90 days of surgery were similar for apixaban and LMWH (3.33 % vs. 4.61 %, p = 0.6). Secondary outcomes demonstrated that the rate of a major bleeding event in apixaban group was 1.31 % and LMWH group was 3.08 %, (p = 0.38). Minor bleeding events in the apixaban group were comparable to the LMWH group (10.60 % vs 10.16 %, p = 0.5). Conclusions: In this real world, urban setting, for women undergoing laparotomy for gynecologic cancer, apixaban as post-operative VTE prophylaxis showed no increase in VTE events and appeared safe with no increase in bleeding events compared to LMWH. This study adds to the literature demonstrating that apixaban is safe and effective for VTE prophylaxis in our gynecologic oncology patients.